Siege Dialogues during the Cold War: Harrison E. Salisbury’s 900 Days and Its Sources - Barskova, Polina (Wiener Slawistischer Almanach, 2021)
This paper reflects on researching the papers of Harrison Salisbury housed at the Rare Book and Manuscript Library at Columbia University. An inquisitive and popular journalist, Salisbury spent nearly twenty years with the United Press (UP), much of it overseas, and was UP’s foreign editor during the last two years of World War II. He was also the The New York Times’ Moscow bureau chief from 1949–1954. This paper addresses his book The 900 Days (1969) that up to this day remains, in spite of its many mistakes and omissions, one of the richest accounts of the intellectual, cultural and emotional life in the city of disaster. Specifically, my inquiry is to figure out how Salisbury worked with his sources other than the Soviet published ones, how he sought information that allowed him to re/construct such a rich, controversial tapestry given the absence of information from behind the “Iron Curtain”. Discoveries of Salisbury’s creative dialogues with Anatoly Darov and Mikhail Diakonov, and inclusion of their versions of the Siege into his book, widen our traditional understanding of tamizdat and open it towards new questions of genre.